Perceptions of South Africa’s master of public health graduates on the degree’s contribution to their leadership at work and in society - Zweigenthal, Virginia; Christofides, Nicola; Dlungwane, Thembelihle; Matlala, Sogo France; Mokgatle, Mathildah Mpata; Opare, Abraham; Patrick, Sean Mark; Schaay, Nikki; Shung-King, Maylene; Tshitangano, Takalani; Rispel, Laetitia (Frontiers in Public Health, 2025)
IntroductionIntegrating public health functions into national health systems is essential to enhance population health. The Master of Public Health (MPH) degree is an important foundation for public health practice in low-and middle-income countries such as South Africa. However, insufficient evidence on individual motivations for undertaking the MPH and the perceptions of graduates on the utility of the degree at work and in society and its contribution to their leadership skills informed this study.MethodsA consortium of academics from eight South African universities developed a self-administered questionnaire to measure inter alia the socio-demographic characteristics, motivations, career paths, perceptions of the utility of the degree, and its contribution to their professional and personal development. The study population comprised the 2012–2016 cohort of MPH graduates from eight universities. Following informed consent, eligible graduates completed an online survey via REDCap. The data were analyzed using Stata.ResultsA total of 221 graduates completed the survey. The mean age of respondents was 35 years, and the majority were from South Africa (53.2%) or other African countries (43.2%). The majority (91.1%) completed the MPH to improve their skills or to promote their personal development for senior management and leadership roles. Approximately 75% used identified leadership skills at work, but only half these skills were obtained from the MPH. Over 80% of respondents positively impacted on their workplace and in society, using skills mostly derived from the MPH in all domains.DiscussionThis cohort of MPH graduates exercised leadership in different settings, but many stated that these skills were not obtained from the MPH programs. The COVID-19 pandemic underscored the need for public health leaders skilled in communication, collaboration, and crisis management, amidst considerations of social justice and equity. Hence, leadership skills need to be intentionally included in MPH programs in South Africa.